The Influence of Website Design, Reliability, and Perceived Ease of Use on E-Retention through the Mediating Roles of E-Trust and E-Satisfaction - Tanjung, Priskilla Maurin Wijaya; Rahayu, Siti; Widjaja, Fitri Novika (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
This study investigates the effects of website design, reliability, and perceived ease of use on customer e-retention in Indonesian e-commerce marketplaces, incorporating customer e-trust and e-satisfaction as dual mediators. Using a quantitative, causal research design, data were collected through an online survey from 294 users of major e-commerce websites, including Shopee, Tokopedia, Lazada, Blibli, and Bukalapak. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Results reveal that website design significantly enhances both customer e-trust and e-satisfaction but does not directly influence e-retention. Reliability has a significant direct and indirect effect on e-retention through trust, while perceived ease of use impacts e-retention primarily through satisfaction. Furthermore, customer e-trust significantly mediates the effects of website design and reliability on e-retention, whereas customer e-satisfaction mediates the effects of website design and perceived ease of use. The model explains 69.6% of the variance in customer e-retention, demonstrating substantial explanatory power. This research contributes to the understanding of how interface quality and psychological mechanisms jointly drive long-term customer behavior in e-commerce. Practically, the findings highlight the importance of enhancing visual design, maintaining service reliability, and simplifying usability to strengthen trust, elevate satisfaction, and sustain customer loyalty.